Analisis Pembelajaran Ilmu Pengetahuan Alam Pada Materi Sistem Tata Surya di Sekolah Dasar - Nelia Reka Pradina; Insan Esa Azyfah; Yuliningsih Yuliningsih; Wahyu Kurniawati (International Forum of Researchers and Lecturers, 2024)
This research is a data collection technique in this research using literature study. The library study collection technique is a study used to collect data and information with various assistance available in the library, for example books, magazines, documents, or reading various journals that are needed. Literature study also studies various reference books and previous research results so that it can be useful for obtaining a material basis regarding the matter to be researched which discusses issues regarding the solar system by providing concise basic concepts. The topics discussed are the characteristics and various members of the planets. solar system. The solar system is one of the materials contained in natural science. In the learning process, the solar system consists of a collection of celestial bodies centered around a star called the sun, and all celestial bodies are connected based on their gravity. There are eight known planets in the solar system, namely Mercury, Venus, Earth, Mars, Jupiter, Saturn, Uranus and Neptune. Based on the position of the planets, there are planets called inner planets and outer planets. The purpose of this article is to analyze the solar system, which includes the definition of the solar system, the characteristics of the members of the solar system, as well as the various planets and their characteristics which will be discussed in detail in the results and discussion sections.